Digital Divide and Risked Communities: A Case Study of the Vulnerabilities of Women in India During the Pandemic - BARSHA BISWAL; Navaneeta Rath (International Journal of Instructional Technology and Educational Studies)
Abstract:Digitalisation is a revolution to change the face of the world. Countries across the globe have accepted this. India too was in her mission of digitalization by launching the flagship program “Digital India” on July 2, 2015.Though India had made a considerable stride in the process, there existed a digital divide in the country on various grounds. Gender was a prominent cause of digital divide in the country. But this became an acute issue during the pandemic when the gendered digital divide showed its ugly face and brought insurmountable issues to women accentuating their vulnerabilities and proving them as a risk community. The present paper aims at unveiling the sex disaggregated digital demography of India, the existing digital divide in the country. It tries to delve out the dynamics behind this gender based digital divide and the way it contributed to increasing vulnerabilities among women during the pandemic. The paper also provides some insight into preparing strategies to overcome this divide and make women digital pro and help them to create an enabling and empowering environment for them. In a nutshell, the paper aims at looking at the situations of digital divide and bringing solutions to them to make women a resilient community as against a risk group. The paper reflects the situation of India during the pandemic at its climax and is based on purely secondary data located and retrieved from articles, reports, blogs.